2011
DOI: 10.4028/www.scientific.net/amr.332-334.1339
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Properties of Polyurethane Nanofibers Nonwoven by Solution Blowing

Abstract: Polyurethane (PU) nanofibers were fabricated by solution blowing. The effects of polymer concentration, gas pressure and temperature on morphology and diameter of fiber were discussed. The results show that the fiber with mean diameters in 100nm- 400nm range was successfully obtained, and when the mass fraction of the solution increases, the diameter of the fiber increases. On the whole, the evenness of the fiber diameter tends to decrease. The gas pressure and the temperature affect the fibers’ diameter, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In this paper, authors have also demonstrated industrial scale solution blowing with PEO and Clarisoy (Soy protein isolate) where, with 328 nozzles of 0.002 inch I.D., authors prepared nonwoven samples in the range of 900-1600 cm 2 in 10 s with solid weight of 5.1 g and fiber diameters varying between 0.5-1.5 µm. Several other authors, like Oliveira et al, (2013) [82], and Guan et al, (2011) [28] also have demonstrated the feasibility of this process with polymers like PLA and PEO; the latter being known for its spinnability, and even with thermoplastic polymer like Polyurethane (PU). Solution blowing depends on various parameters, namely nozzle dimensions, air pressure, collecting distance, and viscoelasticity of the polymer solution [47,74].…”
Section: Solution Blowingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, authors have also demonstrated industrial scale solution blowing with PEO and Clarisoy (Soy protein isolate) where, with 328 nozzles of 0.002 inch I.D., authors prepared nonwoven samples in the range of 900-1600 cm 2 in 10 s with solid weight of 5.1 g and fiber diameters varying between 0.5-1.5 µm. Several other authors, like Oliveira et al, (2013) [82], and Guan et al, (2011) [28] also have demonstrated the feasibility of this process with polymers like PLA and PEO; the latter being known for its spinnability, and even with thermoplastic polymer like Polyurethane (PU). Solution blowing depends on various parameters, namely nozzle dimensions, air pressure, collecting distance, and viscoelasticity of the polymer solution [47,74].…”
Section: Solution Blowingmentioning
confidence: 99%
“…There are various methods available for the fabrication of polymer micro-and nanofibers, namely melt blowing [24,25], electrospinning [26][27][28][29][30][31][32], solution blowing [33][34][35][36][37][38], self-assembly [39], phase separation [40], island in the sea [41], drawing [42], template synthesis, wet spinning, dry spinning, and melt spinning [13,43]. Although the individual fabrication method has its own advantages, electrospinning is the most popular one, because of its relative simplicity and scalability to produce fibers from 1 µm-100 nm reproducibly [44][45][46].…”
Section: Fabrication Of Polymer Fibers: Electrospinning and Solution mentioning
confidence: 99%
“…10 Compared with electrospinning, solution blowing process has signicant advantages such as high productivity due to its high solution feed rate, easy accessibility and low energy consumption due to not using high-voltage equipment. 11 Moreover, the solution blown nanobers are different from the electrospun nanobers and they are commonly curled in three dimensions. 10 In this work, the sulfonated poly(ether ether ketone) (SPEEK) nanobers was prepared using the solution blowing process rstly.…”
Section: Introductionmentioning
confidence: 99%
“…These features considerably enhance the applications in the elds of ltration, 1 sensors, 2-4 biomedicine, 5,6 protective clothing, 7,8 catalysis, and energy generation and storage. [9][10][11] Different techniques have been available for making nanobres, such as drawing, 12 template synthesis, 13 phase separation, [14][15][16] centrifugal-spinning, 17,18 micro bre extrusion, [19][20][21] solution blowing, [22][23][24] chemical vapour deposition [25][26][27] and hydro-thermal. [28][29][30] However, electrospinning is distinct from the others in its simplicity, cost effectiveness, controllability and capability for large-scale production.…”
Section: Introductionmentioning
confidence: 99%